Aerodynamic Study of a Single Groove on the Upper Surface of a NACA 0012 Airfoil at Low Angles of Attack - Wan Nawang, Wan Muhammad Aqil; Yaakub, Mohd Fauzi (Progress in Aerospace and Aviation Technology, 2026)
This study investigates the aerodynamic effects of a single semicircular groove on the upper surface of a NACA 0012 airfoil at low angles of attack (0°–10°) using computational fluid dynamics (CFD) in ANSYS Fluent. The work aims to determine the groove size and chordwise position that enhance lift and reduce drag through passive flow control for UAV and low-speed aerodynamic applications. Three groove diameters (5 mm, 10 mm, and 15 mm) were tested at 25% chord length (0.25c). The 10 mm groove produced the best performance, increasing lift by 3.88% at 6° AoA and reducing drag by 8.84% at 10° AoA relative to the baseline airfoil. The 10 mm groove was then evaluated at chordwise positions of 0.25c, 0.3c, 0.4c, 0.5c, 0.6c, and 0.75c, with the 0.25c position producing the highest lift and the most significant drag reduction. Flow visualization showed that the groove generated a recirculating vortex that energized the boundary layer and delayed flow separation. Validation against the experimental data showed a maximum deviation of 7.26%, supporting the reliability of the two-dimensional CFD model. The study concludes that a properly sized and positioned groove can improve airfoil performance without external energy input, offering practical benefits for aerodynamic design.